Culture and Taxation: Implementation of Tri Hita Karana in Accounting Information Systems for Regional Tax Optimization in Bali - YUDHA, Cokorda Krisna; SANJAYA, I Gusti Ngurah (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the role of Technology Utilization in AIS and the Implementation of Tri Hita Karana Values on Tax Reporting and Regional Tax Optimization in Bali, with a focus on Village Credit Institutions (LPD) in Gianyar and Badung Regencies. The research method used is quantitative, with data collection through closed questionnaires distributed to 122 LPDs as a sample. Data analysis was conducted using the SmartPLS program to test the validity, reliability, and feasibility of the model, and to measure the influence of each variable on the research results. The results of the study show very interesting findings. The SEM-PLS analysis shows that Technology Utilization in AIS and the Implementation of Tri Hita Karana Values show a positive contribution to improving Tax Reporting and Regional Tax Optimization. Analysis of the description of respondents' answers shows responses that only reach the Fair category. Both findings indicate that LPDs can play a role in improving Tax Reporting and Regional Tax Optimization in the future. The current condition shows that LPDs are still not ready to be involved in tax performance in Gianyar and Badung Regencies. These results need to be addressed in further research by seeking stimulus formulations for each LPD. LPD basically supports the involvement of this institution to help improve Tax Reporting and Regional Tax Optimization.